Subsidios a la producción y delegación de la política comercial en una unión aduanera - Méndez-Naya, José (Estudios de Economía, 2016)
By using a reciprocal dumping model, this paper justifies the existing preferential trade agreements as being a reaction to a third country export subsidy. On the other hand, assuming that one of the member countries may set its production subsidies optimally, the effects on welfare derived from the delegation of customs union’s commercial policy are addressed. The main result obtained is that in a non-transferable utility context the union is not sustainable.